Histopathological Spectrum of Oral Cavity Lesions at A Tertiary Care Hospital in South India - Thomas, Beena Mary; Rajagopal, Indu (Annals of Pathology and Laboratory Medicine, 2019)
Background: Oral cavity lesions are usually asymptomatic. Oral cancer is the most common type of cancer among males in India. Proper management of patients begins with an accurate diagnosis and histopathology is considered as the gold standard. The objective is to study the pattern of oral cavity lesions in a tertiary care hospital, Kannur, Kerala. Methods: A 1 Â½ year retrospective study was carried out and included all the oral cavity specimens received in the Department of Pathology. The parameters analyzed were age, gender, site & histopathological diagnosis of the lesion. H & E slides were reviewed. Result: A total of 107 cases were studied. Age ranged from 5 years to 90 years. Males and females were equally affected (M:F = 1.05:1). Buccal mucosa was the commonest site involved. 24 cases (14 malignant,10 benign and 4 premalignant) were neoplastic and the rest were non neoplastic. Squamous cell carcinoma (11.2%) was the most common malignant lesion with favoured sites being buccal mucosa followed by tongue and tonsil. Conclusion: Good clinical examination combined with accurate histopathological study is essential to confirm the nature of the lesion.